PENGARUH KEBIJAKAN HUTANG, KEPUTUSAN INVESTASI, DAN TOTAL ARUS KAS TERHADAP NILAI PERUSAHAAN (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Tahun 2011-2013) - Noviadinar Imariza Rahmawati, 10.05.52.0190; Himawan, Arif (Students' Journal of Accounting and Banking, 2016)
The purpose of this study was to examine and analyze the effect of the debt policy, investment decisions, and the total cash flow to the firm value. Every company has a goal to maximize the welfare of the owners by raising the value of the company. The population in this study are all manufacturing companies listed in Indonesia Stock Exchange period 2011 to 2013. The sample was conducted using purposive sampling. The samples used were 107 manufacturing companies. The data used is secondary data obtained from the Financial Statements and the Indonesian Capital Market Directory (ICMD). The analysis technique used is multiple linear regression analysis. The results of this study indicate that the debt policy significant negative effect on the value of the company, investment decisions are significant negative effect on firm value, and total cash flow significantly positive effect on firm value.Keywords: Debt Policy, Investment Decisions, Total Cash Flow, Enterprise Value